Application of Prescription Reviews for Traditional Chinese Medicine to Improve Medical Disputes and Patient Satisfaction. (7th July 2022) - Yu, Chunlan; Xu, Shanmei
Abstract : Objective . Medical disputes and patient satisfaction are related to inappropriate prescribing practices. We aim to investigate the clinical application of prescription reviews for traditional Chinese medicine (TCM). Method . TCM prescriptions performed prescription reviews in 372 patients from the year 2019 to 2020 were set as the observation group and those from the year 2017 to 2018 without prescription reviews as the control group ( n = 341). According to the Criteria for Assessing Prescription Quality in Chinese Hospitals (CAPQCH) items, "Irrational" and "Rational" TCM prescriptions were determined mainly based on the following category: nonstandard prescriptions, inappropriate prescriptions, and hypernormal prescriptions. The incidence of medical disputes and the degree of patient satisfaction were compared between the two groups. Result . No difference was found in age and gender between the control group and the observation group. The number of irrational TCM prescriptions from the year 2017 to 2020 was 6, 8, 2, and 3, respectively, with the percentage of 3.725%, 4.480%, 1.201%, and 1.446%. The irrational rate in the observation group (1.344%) was significantly lower than that in the control group (4.106%). Specifically, a higher rate of nonstandard prescriptions was revealed in the control group as compared with the observation group. Moreover, a reduced incidence of medical disputes was revealed in the observation group relative to the control group accompanying with the increased degree of patient satisfaction. Conclusion . Prescription reviews have high application value in the management of Chinese pharmacies, which can improve the rationality of prescriptions, increase patient satisfaction, and reduce medical disputes.